Transformasi Visual Lambang-Lambang Partai Politik Islam (1955 – 2004) - Reiza D. Dienaputra (ITB Journal Publisher, LPPM ITB, 2009)
The existence of Islamic political parties in the field of Indonesian politics has a very long history. The Islamic political parties had actually been found before the independence. Their quantitatively significant development, however, takes place after the era of independence. Throughout the development, there have been many researches on the existence of Indonesian political parties. Among those researches, however, it seems that there has never been a research carried out by employing visual sources such as symbols of political parties. These symbols are often neglected. They are as if something which cannot be explored and tend to be merely a complement for a political party. In fact without any symbols, it is impossible for a political party to follow election. Therefore, a symbol plays a very important role since it is not only to show the identity of a political party but also to fulfill the provisions of legislation. For the above reasons I am interested in carrying out this research. In relation to that, the research employs both political and cultural approaches in order to produce interesting findings about political parties’ symbols. Based on the study upon the symbols of Islamic political parties participating in 1955 – 2004 elections, it is found that the visualization of the symbols undergoes an incredibly dynamic development in both element and sense of form. There are several factors which cause the coming out of visual dynamics on political parties’ symbols such as the experience of national history, cultures built up in the society, and the improvement of design technology. The dynamics of the element of form shows a visual reality that the moon and the star, which are usually regarded as the representation of Islamic political parties, are not always used by Islamic political parties and they are not only used by them as their symbols as well. Furthermore, the dynamics of the sense of form also show interesting finding that the star as the element of form does not constantly produce the same sense of form.